(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Correction of refractive errors of the eye by reshaping the cornea using a number of techniques such as surface laser or LASIK and others. Less than (40-50) seconds and with high accuracy . In this project we found Myopia was more common than hyperopia, treatment of refractive error by excimer laser was slightly higher in females than in males and refractive errors were more common among the students